Paths to modernity and the secularization issue - Schwinn, Thomas (Analyse & Kritik, 2017)
In the lively debate of the last two decades about the validity of the ‘secularization thesis’, the comparison between Europe and the USA plays a central role. The high level of religiosity beyond the Atlantic has put under pressure the assumption of the loss of importance of religion in modernity, which had been prevalent for a long time. In this debate, the connection between the differentiation theory and sociology of religion, which has already been discussed by the classics of the discipline, has attracted too little attention. This article takes up this desideratum and proposes, following Max Weber, a theory of differentiation which is able to cover the variety of religious processes. This proposed analysis will be made concrete with reference to the different paths to modernity of Europe and the USA and the related importance of religion.